(untitled) (Research, Society and Development, 2023)
Occupational accidents and occupational diseases stand out in society because of their deleterious effect on the physical integrity of the human being, in addition to the direct and indirect costs that fall on the government and organizations. The implementation of ISO 45001 acts as a management tool with the potential to improve the organization’s performance for occupational health and safety outcomes, as it reduces the risks of occupational accidents and diseases. The objective of this research was to identify the main critical factors related to the implementation of the ISO 45001 Standard in the view of its managers, in companies in the pharmaceutical sector, located in the Southeast region of Brazil. The methodological approach used was qualitative research with a multiple case study, based on semi-structured interviews. As a result, it was evidenced that the main critical factors for the implementation of ISO 45001 are directly related to the level of commitment of the company’s senior management to occupational health and safety issues. Thus, the propositions resulting from the study suggest that the greater and more effective the commitment of leadership to occupational health and safety, the less complex the implementation of iso 45001 and the greater the adherence of managers and employees involved.